Literacy and the Problem of Linguistic Prejudice - Cagliari, Luiz Carlos [UNESP] (Springer Nature, 2023)
It is necessary to discuss linguistic variation problems and related social prejudice starting from the acquisition of oral language. Everybody learns a language variety through a process of interaction with their family and the social environment where they live. The children take their native variety to school for the literacy studies. The literacy classes used to comport students from different dialects. The different ways of speaking emerge when the students talk to each other. Sometimes, cultural and socioeconomic differences establish a complicated relation among people: some become arrogant, some become stigmatized. The students will be taught in a standard variety and use the orthography. The teacher will teach what is new without destroying the student’s linguistic abilities. Certainly, there will be problems of relationships among the students caused by the way they speak. Dialect variations provoke situations of verbal discrimination leading to a situation of linguistic prejudice. If these sentiments are not adequately controlled since the beginning of schooling, the relationship between mates of the class may root bullying, discrimination and prejudice in subsequent years. It is absolutely necessary to obtain from literacy the harmony among speakers from different linguistic varieties in school and in life.
Keywords: Linguistic prejudice; Literacy; Reading; Spelling